Effect of maternal Tdap on infant antibody response to a primary vaccination series with whole cell pertussis vaccine in São Paulo, Brazil - Lourdes R.A. Vaz-de-Lima (Vaccine: X, 2021)
Background: Maternal Tetanus, diphtheria, and acellular pertussis (Tdap) vaccination provides antibody transfer to newborn infants and may affect their antibody response to the primary vaccination series. This study aimed to assess the effect of Tdap vaccination during pregnancy on infant antibody response to the whole cell pertussis (DTwP) primary series. Methods: Plasma from 318 pregnant women (243 Tdap-vaccinated and 75 unvaccinated) and their infants (cord blood) was collected at delivery; infant blood was again collected at 2 and 7 months, before and after their primary DTwP series. Anti-pertussis toxin (PT), pertactin (PRN), filamentous hemagglutinin (FHA), fimbriae 2/3 (FIM) and adenylate cyclase toxin (ACT) IgG antibodies were quantified by a microsphere-based multiplex antibody capture assay and anti-PT neutralizing antibodies by the Real Time Cell analysis system. Results: Infant geometric mean concentrations (GMCs) of IgG anti-Tdap antigens were significantly higher (p < 0.001) among the Tdap-vaccinated (PT: 57.22 IU/mL; PRN: 464.86 IU/mL; FHA: 424.0 IU/mL), versus the unvaccinated group (4 IU/mL, 15.43 IU/mL, 31.99 IU/mL, respectively) at delivery. Anti-FIM and ACT GMCs were similar between the two groups. At 2 months of age, anti-PT, PRN, and FHA GMCs remained higher (p < 0.001) in the Tdap-vaccinated group (12.64 IU/mL; 108.76 IU/mL; 87.41 IU/mL, respectively) than the unvaccinated group (1.02 IU/mL; 4.46 IU/mL; 6.89 IU/mL). However, at 7 months, after receiving the third DTwP dose, the anti-PT GMC was higher (p = 0.016) in the unvaccinated group (7.91 IU/mL) compared to the vaccinated group (2.27 IU/mL), but without differences for anti-PRN, FHA, FIM and ACT GMCs. Conclusion: Elevated antibody levels suggest that maternal Tdap vaccination might protect infants until 2 months of age. Reduced anti-PT levels at 7 months indicate potential blunting of immune response in infants. Surveillance would help determine if blunting alters vaccine immunity and impacts pertussis prevention in infants.